Peru : 2011 Article IV Consultation: Staff Report; Supplement; and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation reports that Peru's activity is expected to decelerate in 2011-12 to slightly below trend while inflation declines toward the target and the external current account deficit remains contained. Short-term risks are markedly to the downside given global uncertainty. Once international turbulence subsides, strong growth prospects and abundant international liquidity could increase capital inflows. The fiscal policy focus on undertaking the capital expenditures budgeted for 2011 is appropriate. Macroeconomic stability, growth potential, and social inclusion could be strengthened by adopting an ambitious reform agenda.